COMPREHENSIVE INDEX OF QUALITY OF ROLLED STEEL AND ITS APPLICATION - A. B. Steblov (Литьë и металлургия)
The concept of an integrated indicator of quality of rolled metals, for example bearing steel 1.3520(EN), as a set of properties reflecting the quality of the profile geometry, surface defects, macro and microstructure and mechanical properties was considered. The qualitative evaluation of the achieved quality level, the calculation of the probability of occurrence of defects was made. The methodology of technology management on the basis of statistical relations of the studied quality indicators with parameters of industrial technologies in steelmaking and rolling shops was established.